Mining Conflict and Sustainable Development: A Review of Case Studies and Theoretical Framework - Ilham Samanlangi; Ramdan Yusuf; Ilwandri; Fantoni; Adikarya, Wiwid Suryono (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Mining has significant impacts on the environment and communities. Conflicts often arise between mining companies, governments and local communities over issues such as evictions, environmental damage and pollution. These conflicts can hinder sustainable development efforts. This research aims to review the literature on mining conflicts and sustainable development. This research uses the literature review method. The literature reviewed includes scientific articles, books, and research reports. The results of this study conclude that mining conflicts can hinder sustainable development by causing social instability, environmental damage and investment barriers. To address these conflicts, we recommend an approach that involves all stakeholders, emphasises good governance, responsible environmental management, empowerment of local communities, and effective dispute resolution mechanisms